Nature-based education: using nature trails as a tool to promote inquiry-based science and math learning in young children. (2nd October 2019) - Lee, Carole K.; Ensel Bailie, Patti
Abstract: Nature trails can be used as a tool for young children to learn about inquiry-based science and math in an open and natural environment. A nature trail provides the opportunity for children to develop their gross motor skills by walking, hiking or playing on the trail and enhance social skills by doing outdoor activities with their friends. The nature trail activities described in this paper are geared toward pre-K to grade 3 children and created by the pre-service early childhood teachers (PSECTs) who attended a five-week nature-based education course held in late spring/early summer term. The nature-based activities supported not only the Maine's Early Learning and Development Standards (MELDS) but also the Next Generation Science Standards (NGSS), and Common Core Math Standards (CCMS). The PSECTs enjoyed creating the activities and appreciated the positive feedback from their classmates when they were trying out the activities on the trail. Creating a nature trail for young children was a new and eye-opening learning experience for all the PSECTs and they were encouraged as teachers to build new nature-based activities that would benefit their future students.